2011
DOI: 10.3109/00365599.2011.584551
|View full text |Cite
|
Sign up to set email alerts
|

Urinary lithogenesis risk tests: Comparison of a commercial kit and a laboratory prototype test

Abstract: The new commercial NefroPlus test offers fast and cheap evaluation of the overall risk of development of urinary calcium-containing calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
2
0
1
Order By: Relevance
“…We found that 47.5% of our subjects had high CaUCR using previously established criteria (Table 1). Previous studies demonstrated that nearly 100% of patients who met these criteria were stone-formers [16,17,18]. We also found that subjects who better adhered to the MedDiet had a significantly decreased CaUCR.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We found that 47.5% of our subjects had high CaUCR using previously established criteria (Table 1). Previous studies demonstrated that nearly 100% of patients who met these criteria were stone-formers [16,17,18]. We also found that subjects who better adhered to the MedDiet had a significantly decreased CaUCR.…”
Section: Discussionsupporting
confidence: 66%
“…Ca, P and Mg were measured using inductively coupled plasma tandem atomic emission spectrometry (ICP-AES), Ur was determined using the uricase method, Ox was determined using the oxalate oxidase/peroxidase method (LTA, Milano, Italy), and Cit was determined using an enzymatic assay (Biosystems, Barcelona, Spain). Lithogenic urine was defined by a high calcium salt urinary crystallization risk (CaUCR) or a high uric acid urinary crystallization risk (UrUCR), in accordance with the criteria indicated in Table 1 [16,17,18,19].…”
Section: Methodsmentioning
confidence: 99%
“…Эта группа маркеров ЛА является самой многочисленной и наиболее успешной. Четыре представителя данной группы дошли до этапа клинического применения: • BONN-Risk, реализованный в аппарате Urolizer [65,66]; • ULR-тест, реализованный в лабораторном наборе NefroPlus [67]; • тест подавления агломерации оксалата кальция, применяемый в клинике Ochsner Renal Stone Clinic (Луизиана, США) [68,69]; • Литос-тест, применяемый в России [8,70].…”
Section: тесты индуцированной кристаллизации мочиunclassified
“…Several studies used these indexes, including the calcium/citrate ratio, the ion activity product of calcium oxalate (AP[CaOx]), and calcium phosphate (AP[CaP]), to compare stone-forming children and adults with healthy controls, and found significant differences [7, 911]. Furthermore, previous studies have shown cut off values for urinary solute concentrations that makes urine prone to crystallize in an in vitro model [12, 13].…”
Section: Introductionmentioning
confidence: 99%